Analytical Study of Primary Health care in Developing Countries: Exploring Medicines and Health Care Disparities in Developing Countries (Journal of Advances and Scholarly Researches in Allied Education, 2021)
There have been recurring issues between medicine (treatment) and public health(prevention). This is mainly due to heavy competition on the development of value-added medicines bymost modernized pharmaceutical companies. Most of the medicines have been manufactured under thestrict guidelines of international monitoring agencies, in order to keep safety and security. Medicines arefor maintenance of health care at different stages of the life cycle. Irrespective of cost, medicines areused at primary, secondary, and territory levels of health treatment. Contemporary medicine appliesbiomedical sciences, biomedical research to diagnose, treat, and prevent injury and disease. But, due tothe cost and market availability, it is not possible to use many lifesaving biologics. Primary health-caremedical services are extended by physicians, physician assistants, nurses, or other health professionalswho have the first contact with a patient seeking medical treatment or care. About 90 of medical visitscan be treated by the primary care provider. These include treatment of acute and chronic illnesses,preventive care, and health education for all ages and both sexes. Availability of medicines and clinicalpractice varies across different geographic locations of the world, and the availability and cost ofmedicines vary accordingly. Biologic drugs are highly developed in the Western world. While indeveloping countries such as Asia-pacific and Africa, the population relies on traditional pharmaceuticalmedicines due to their low cost.